Pembuatan Sabun Padat Berbasis Eco Enzyme sebagai Upaya Pengelolaan Limbah Domestik - Susilawati, Susilawati; Agustina Tanjung, Azahra; Alya Razali, Indira; Angelina Br Tarigan, Nadia; Nabila, Zahra (Institute for Research and Community Service (LPPM) of the Islamic University of Jember, 2026)
The issue of household organic waste remains a challenge in environmental management at the community level. This community service activity aims to provide practical solutions through training in the production of eco-enzymes from fruit and vegetable scraps and their use as ingredients in environmentally friendly solid soap. This activity uses a participatory approach through the stages of problem identification, planning, implementation, and evaluation. Eco enzymes are made by fermenting fruit and vegetable waste with a composition of 60% water, 10% natural sugar, and 30% organic material for three months. The resulting fermented liquid is then used as a substitute for water in the saponification process using olive oil, coconut oil, and sodium hydroxide to form solid soap, which is then molded and cured. Evaluation is carried out descriptively through observation of the success of the fermentation process and the physical characteristics of the soap produced. The results of the activity showed that eco enzyme can be used in soap formulations and produces small round products (3 cm in diameter; ±25 grams) with a solid texture, neat surface, natural pastel pink color, and a light aroma characteristic of fermentation without synthetic fragrances. In the short term, this activity produced real product samples that can be used in daily needs. In the long term, this practice has the potential to reduce household organic waste and open up opportunities for developing home-based businesses based on environmentally friendly products. This activity also demonstrates the role of institutions in providing concrete solutions to domestic environmental problems